(untitled) (American Journal of Smart Technology and Solutions, 2025)
Marine communication systems have been grappling with obstacles for a while now. Issues like restricted weak connectivity, are common problems in far-off oceanic areas where delays are high, and reliability is a concern too. These challenges hinder the functioning of contemporary marine systems that heavily depend on swift and continuous data transfer for instant decision-making and navigation accuracy. Cutting-edge innovations, like quantum computing and the generation of wireless networks, offer hope to transform marine communication by offering sophisticated solutions to these barriers. This analysis delves into how autonomous systems are used in activities and looks into the ways quantum computing and 6th generation technologies can help alleviate communication challenges in that field. Quantum computing brings data processing and encryption features, to the table while 6th generation technology provides low latency and high speed connectivity crucial for seamless real time operations of autonomous systems. The document emphasizes the potential between these technologies and talks about how they could lead to an effective and safe communication network, for maritime purposes. Moreover talking about the difficulties and how to blend quantum and 6th generation technologies, in settings has been emphasized in the review as well as discussing future research paths that could be taken in this area of study. By tackling these challenges it is believed that the maritime sector could make strides forward in enhancing the performance of autonomous systems leading to safer and more effective worldwide maritime activities.